Acetamiprid-Induced Toxicity Thresholds and Population Sensitivity in Trichogramma dendrolimi: Implications for Pesticide Risk Assessment - Yan Zhang; Jiameng Ren; Shenhang Cheng (Insects)
Trichogramma dendrolimi, a key egg parasitoid for lepidopteran pest control, faces potential risks from neonicotinoid insecticides like acetamiprid used in integrated pest management (IPM). This study evaluated acetamiprid’s acute and sublethal toxicity to T. dendrolimi and assessed population-level risks via species sensitivity distribution (SSD). Acute toxicity assays using glass-vial residues revealed a 24 h LC50 of 0.12 mg a.i. L−1 for adults, three orders of magnitude below the maximum field rate (100 mg a.i. L−1). Sublethal exposure (1/2–1/100 LC50) significantly reduced parasitism and emergence rates (NOEC = 2.3 μg a.i. L−1) but did not affect offspring survival. Acetamiprid also shortened offspring development at 11.5–57.5 μg a.i. L−1. SSD analysis identified T. dendrolimi as the most sensitive parasitoid to acetamiprid (HC5/HC50) = 0.11/5.88 mg a.i. L−1), with field rates (30–100 mg a.i. L−1) indicating a potentially affected fraction (PAF) of 76.8–97.9%. These findings underscore the need to integrate sublethal effects into pesticide regulations to conserve parasitoid-mediated ecosystem services.